Exosomes from N-Myc amplified neuroblastoma cells induce migration and confer chemoresistance to non-N-Myc amplified cells: implications of intra-tumour heterogeneity. Issue 1 (1st December 2019) - Fonseka, Pamali; Liem, Michael; Ozcitti, Cemil; Adda, Christopher G.; Ang, Ching-Seng; Mathivanan, Suresh
ABSTRACT: Neuroblastoma accounts for 15% of childhood cancer mortality. Amplification of the oncogene N-Myc is a well-established poor prognostic marker for neuroblastoma. Whilst N-Myc amplification status strongly correlates with higher tumour aggression and resistance to treatment, the role of N-Myc in the aggressiveness of the disease is poorly understood. Exosomes are released by many cell types including cancer cells and are implicated as key mediators in cell-cell communication via the transfer of molecular cargo. Hence, characterising the exosomal protein components from N-Myc amplified and non-amplified neuroblastoma cells will improve our understanding on their role in the progression of neuroblastoma. In this study, a comparative proteomic analysis of exosomes isolated from cells with varying N-Myc amplification status was performed. Label-free quantitative proteomic profiling revealed 968 proteins that are differentially abundant in exosomes released by the neuroblastoma cells. Gene ontology-based analysis highlighted the enrichment of proteins involved in cell communication and signal transduction in N-Myc amplified exosomes. Treatment of SH-SY5Y cells with N-Myc amplified SK-N-BE2 cell-derived exosomes increased the migratory potential, colony forming abilities and conferred resistance to doxorubicin induced apoptosis. Incubation of exosomes from N-Myc knocked down SK-N-BE2 cells abolished the transfer of resistance to doxorubicin induced apoptosis. These findings suggest that exosomes could play a pivotal role in N-Myc-driven aggressive neuroblastoma and transfer of chemoresistance between cells. Abbreviations : RNA = ribonucleic acid; DNA = deoxyribonucleic acid; FCS = foetal calf serum; NTA = nanoparticle tracking analysis; LC-MS = liquid chromatography–mass spectrometry; KD = knockdown; LTQ = linear trap quadropole; TEM = transmission electron microscopy